Analysis of Difficulties in Solving the Story Problem of a System of Two-Variable Linear Equations Based on Newman's Theory - Yesi Setyorini; Slamet Hw (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2023)
This research aims to describe students' difficulties in solving the story of a system of two-variable linear equations based on Newman's theory. This research is a qualitative research with a descriptive approach. Tests, interviews, and documentation are used as data collection processes. Data analysis techniques use data reduction, data presentation, and conclusions. The results of this research show that all mistakes based on Newman's theory are made by students. Final answer writing errors are the most common mistakes made by students with a percentage of 25.35%. Reading errors were made 15.04%, comprehension errors 16.16%, transformation errors 21.45%, and process skills errors 22.01%. Thus, students are expected to study harder and practice more questions to avoid mistakes in solving problems.